(untitled) (Journal of Comparative & International Higher Education, 2022)
The outcome of international education attracts increasing interests among scholars in the perceived employability and education-to-work transition. Yet, there is a lack of empirical studies focusing on understanding international students’ perceived employability and the strategies to improve their employability. The purpose of this study is to explore the perceived employability and its factors (e.g. demographic factors, educational factors, work-related factors, language and U.S. experience factors, and family factors) among international students in the U.S. Also, the study examines how gender moderates the relationships between perceived employability and other factors. A survey was conducted among international students at a midwestern public university in the U.S. and 138 participants’ responses were included in the data analysis. The result shows that international students are confident in their employability. Interestingly, compared to female international students, the advantages brought by being in the field of engineering or having more work experiences are mainly for males.